Knowledge transfer of advances in applied health and science - Macnab, Andrew John (GHMJ (Global Health Management Journal), 2018)
Abstract is not required for this Editorial. Below are the summary and keywords the journal provides for insight to our reader.  Summary: The editorial highlighted the practice of starting Global Health Management Journal's edition with selected papers from the prestigious International Conference on Applied Science and Health. The journal follows a gold standard for the peer-review process, ensuring the publication of high-quality research. The primary goal of the journal is to facilitate knowledge transfer and dissemination of advances in applied health and science. The editorial also provides a succinct summary of the key research findings from the selected papers presented at the conference. This approach not only reinforces the journal's dedication to academic rigor but also serves as a platform for sharing valuable insights and advancements in the field of applied health and science. Accepted: 27 June 2018. Keywords: Global Health Management Journal International Conference on Applied Science and Health Gold Standard Peer Review Knowledge Transfer Advances in Applied Health and Science